2020
DOI: 10.1111/jfs.12787
|View full text |Cite
|
Sign up to set email alerts
|

Application of ohmic heating for the inactivation of microbiological hazards in food products

Abstract: Ohmic heating has long been used to inactivate pathogens in food products. Several research investigations on the use of ohmic heating technology in the inactivation of microbial hazards in food products are discussed in this review. These studies are discussed under the following sub-headings: (a) inactivation of microbiological hazards, (b) in combination treatments with other sanitizing technologies, and (c) mathematical modeling, all of which are of long-standing interest. In this review, we evaluate ohmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Ohmic heating has also been used in combination with other methods for years. Shin et al [44] reviewed the hurdle technologies based on ohmic heating in food processing applications. They reported that the pathogen inactivation rate was significantly higher when the ohmic heating was used in combination with other [45] studied the pressureohmic-thermal-sterilization treatment of low-acid foods like vegetable purees and reported its effectiveness in controlling bacterial endospores.…”
Section: Ohmic Heating As Hurdle Technologymentioning
confidence: 99%
“…Ohmic heating has also been used in combination with other methods for years. Shin et al [44] reviewed the hurdle technologies based on ohmic heating in food processing applications. They reported that the pathogen inactivation rate was significantly higher when the ohmic heating was used in combination with other [45] studied the pressureohmic-thermal-sterilization treatment of low-acid foods like vegetable purees and reported its effectiveness in controlling bacterial endospores.…”
Section: Ohmic Heating As Hurdle Technologymentioning
confidence: 99%
“…But even worse than Salmonella, C. jejuni may survive on chicken breast meat after 10 minutes of heating in boiling water (de Jong et al, 2012). Moreover, it has been established that the cold spot does not always appear in the geometrical centre of the product during OH (Choi et al, 2020;Salengke & Sastry, 2007) and foodborne pathogens can survive in those spots for a long time (Shin et al, 2020). That is why it is critical to understand the heating behaviour of chicken meat during OH and the factors that influence it.…”
Section: Abbreviationsmentioning
confidence: 99%